The chemical bond : fundamental aspects of chemical bonding - Frenking, G. (Gernot); Shaik, Sason S., 1943- (Wiley-VCH Verlag, 2014)
A unique overview of the different approaches used for describing a chemical bond, including molecular-orbital based, valence-bond based, ELF, AIM and density-functional based methods. It takes into account the many developments that have taken place in the field over the past few decades due to the rapid advances in quantum chemical models and faster computers.